1957
DOI: 10.1039/jr9570001647
|View full text |Cite
|
Sign up to set email alerts
|

312. Further investigations in the butenyl–boron trichloride system

Abstract: Gerrard, La##ert, and Silver. 1647* The composition (i.e., relative percentages of Iand 3-methylallyl compounds) of the product is shown in Table 2 and similarly for subsequent reactions involving 1-and 3-methylallyl derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1958
1958
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…] and ¿erf-butyl (61, 64) dichloroboronites could not be obtained, although analytical evidence [R = f-C3H7 (64), s-C4H9 (61)] and isolation of a pyridine complex [R = n-CeHi3(CH3)CH (64)] at -80°C. demonstrated the existence of some of these at low temperatures; similar evidence could not be obtained for the ¿erf-butyl (61), 1-and 3-methylallyl (74), benzyl (7), or carbethoxymethyl (52) dichloroboronites. The failure to obtain carbalkoxy-substituted alkyl dichloroboronites was attributed to the competing ester-fission reaction (see Section XI) (52).…”
Section: Hydrocarbonsmentioning
confidence: 71%
See 3 more Smart Citations
“…] and ¿erf-butyl (61, 64) dichloroboronites could not be obtained, although analytical evidence [R = f-C3H7 (64), s-C4H9 (61)] and isolation of a pyridine complex [R = n-CeHi3(CH3)CH (64)] at -80°C. demonstrated the existence of some of these at low temperatures; similar evidence could not be obtained for the ¿erf-butyl (61), 1-and 3-methylallyl (74), benzyl (7), or carbethoxymethyl (52) dichloroboronites. The failure to obtain carbalkoxy-substituted alkyl dichloroboronites was attributed to the competing ester-fission reaction (see Section XI) (52).…”
Section: Hydrocarbonsmentioning
confidence: 71%
“…in an inert solvent such as n-pentane. It has been demonstrated with a selection of primary [R = n-C3H7 (64); n-C4H9, f-C4H9 (61); n-C5Hu (2); ¿-C4H9CH2, n-C8H17 (64); = 2, CH2=C(CH3)CH2 (71); CH3CH=CHCH2, CH2=CHCH2CH2 (74); CH=CCH2 (71); C1(CH2)2 (46); C1(CH2)3 (2); C1(CH2)« (46); C1(CH2)5, CH2C1CHC1CH2 (2); CC13 (22); CF,CH2 (4); C2H6OOCCH2, C2H6OOC(CH2)2 (52)] and also secondary alcohols [R = s-C4H9 (61); f-C3H7(CH3)CH, ¿-C4H9(CH3)CH (64); n-C6H13(CH3)CH (60); CH2=CH(CH3)CH ( 74 Exceptions were those alcohols [R = C6H5CH2 (7), CeHs(CH3)CH (60)] which have a propensity for preionization, when the major product was the alkyl chloride (equation 3), this being the exclusive stoichiometry for an unsubstituted tertiary alcohol (R = ¿-C4H9 ( 61)). Boron trichloride may, however, be used for the preparation of tert-alkyl (as well as less highly branched) borates, by adding the trichloride (1 mole) to a mixture of the alcohol and pyridine (3 moles of each) in an inert solvent such as n-pentane, chloroform, or methylene dichloride at low temperature ( -10°to -80°C.…”
Section: Hydrocarbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, treat~nent of the allyl ether of guaiacol with BF?.2CH,COzH a t 68" gave 38% of eugenol as well as some guaiacol, 6-allylguaiacol, and the allyl ether of allylguaiacol or eugenol (12). Also, allyl phenyl ether a t -80' was converted by boron tricliloride exclusively to o-allylphenol (13). Furthermore, a recent study (14) showed that boron trichloride effected the intramolecular rearrangement in high yields (90-98%) of allyl phenyl ether to 2-allylphenol, ally1 P-tolyl ether to 2-allyl-4-methylphenol, allyl 2,6-dimethylphenyl ether t o a mixture of 2,G-dimethyl-3-allylphenol and 2,G-dimethyl-4-allylphenol, and also allyl nlesityl ether t o S-allylmesitol.…”
Section: Introductionmentioning
confidence: 99%